Application of taxonomic method for the analysis of economic cohesion in the European Union in 2007 - Pawlas, Iwona (Publishing House of the Wrocław University of Economics, 2009)
It was agreed in the Treaty of Rome establishing the European Economic Community that the integration process should bring about diminishing regional disparities among member states. At that time it was believed that market me-chanism itself would help achieve the goal of inner cohesion, so no special policies or actions were implemented [Pelkmans 2006]. Gradual development of the European Communities, however, resulted in a growing gap between the rich and the poor member economies. That is why Structural Funds and – later – Cohesion Fund were introduced [Nowak, Milczarek (eds.) 2006]. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 362-369